Aerobic Exercise Increases Release of Growth Hormone in the Blood Circulation in Obese Women - Adi Pranoto; Purwo Sri Rejeki; Muhammad Miftahussurur; Ghana Firsta Yosika; Mufarrihul Ihsan; Lilik Herawati; Ilham Rahmanto; Shariff Halim (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physical exercise is one of the modulators in increasing the release of growth hormone (GH) levels in blood circulation, but the effective exercise model for obese subjects is still being debated. Therefore, this study aims to prove the effect of aerobic exercise on increasing the release of GH levels in the blood circulation in obese women. A total of 20 obese adult women, aged 21.00 ± 1.08 years were selected to be subjects in the study and were given one aerobic exercise intervention by running on a treadmill at moderate-intensity (60-70% HRmax) for 40 minutes. The ELISA method was used to measure the release of GH levels in all samples (pre- and post-exercise). Statistical analysis in this study used an independent sample t-test with a significant level of 5%. The results showed that the release of GH levels in the blood circulation was found to be higher in post-exercise compared to pre-exercise after one session of aerobic exercise (484.92±128.29 vs 892.63±273.54 pg/mL; p=0.001) and has a large effect size with a Cohen's d value of 1.909. GH levels in the post-exercise blood circulation in the aerobic exercise group (Exr) were also found to be higher than the GH levels in the control group (Ctr) (892.63±273.54 vs 542.97±140.01 pg/mL; p=0.003) and has a large effect size with a Cohen's d value of 1.609. This study proves that one session of aerobic exercise with moderate intensity increases the release of circulating GH levels in obese women. Therefore, aerobic exercise with moderate intensity can be used as an alternative therapy option to increase the release of circulating GH levels in individuals with obesity.